Diffuse Capillary Malformation in Association with Fetal Pleural Effusion: Report of Five Patients. Issue 1 (January 2015) - Rork, Jillian F.; Alomari, Ahmad I.; Mulliken, John B.; Fishman, Steven J.; Liang, Marilyn G.
Abstract Capillary malformation (CM) can be a "red flag" for several syndromic vascular anomalies. We identified a subset of patients with diffuse CM and fetal pleural effusion and documented the type of CM, the etiology of the pleural effusion, the potential syndromic diagnosis, and outcome. Patients with a history of CM and fetal pleural effusion were identified by searching the database of patients evaluated at the Vascular Anomalies Center at Boston Children's Hospital. Standardized patient interviews and a retrospective review of records, photographs, and imaging studies were conducted. Five patients had diffuse CM and fetal pleural effusion. Two patients had macrocephaly‐CM (M‐CM), one had features of M‐CM and CLOVES (congenital lipomatous overgrowth, vascular malformations, epidermal nevi, and spinal/skeletal anomalies and/or scoliosis), and one had diffuse CM with overgrowth. The pleural fluid was chylous in four patients. One patient had thoracic lymphatic malformation. Recurrent effusion occurred in one patient coincident with pneumonia at age 11 years. Four patients had a history of reactive airway disease and episodic pulmonary infections. The diagnosis of vascular anomaly–overgrowth syndromes, particularly M‐CM, should be considered in neonates with fetal pleural effusion.